A inovação pedagógica como meta dos dispositivos de formação a distância - Joana Peixoto (EccoS – Revista Científica)
A program on distance education is not neutral and cannot be reduced to a technological artifact that acts as an ordinary support. It happens to be a context of mediations that cooperates for the development and even the meaning of the actual performance. This article proposes the adoption of a concept of dispositive while dealing with the possibilities of pedagogic innovation within the distance education programs with the use of Information and Communication Technologies. Such approach intends to overcome the technological determinism by taking into account the thesis that a change cannot be considered as an ultimate object, but as an integral process of the learning programs.